Genetic characterization and virulence determinants of multidrug-resistant NDM-1-producing Aeromonas caviae - Hu, Xinjun; Zhang, Huanran; Liu, Yi; Liu, Xiaojing; Qiao, Jie; Ge, Haoyu; Zhao, Junhui; Ma, Xiaohan; Chen, Mantao; Liu, Ruishan (Frontiers in Microbiology, 2023)
The emergence of carbapenemase significant threaten public health. It is prevalent worldwide but rare in Aeromonas caviae. Unlike most bacterial species, A. caviae has two distinct flagella systems, which are closely related to biofilm formation. The ability to form biofilms on host tissues or inert surfaces constitutes an important cause of many persistent infections, causing difficulties in clinical treatment. Here, we report a multidrug-resistant (MDR) A. caviae carrying blaNDM-1 with new sequence type 1416. The strong ability of biofilm formation of FAHZZU2447 was verified by crystal violet assay. The resistome profile and location of blaNDM-1 gene were determined by antimicrobial susceptibility testing, S1 nuclease pulsed-field gel electrophoresis (S1-PFGE) and southern blotting, respectively. Moreover, the strain underwent whole-genome sequencing to identify its genomic characteristics. And the blaNDM-1 gene located on a ~243 kb plasmid with genetic context IS1R-blaNDM-1-ble-trpF-dsbD-hp-sul1-qacE. Phylogenetic analysis indicated the transmission of A. caviae in China, Japan and Thailand. Our study aimed to elucidate the genomic features of blaNDM-1-producing A. caviae, clarify the distribution of A. caviae worldwide and emphasize the harmfulness of biofilm formation to the clinic. Further comprehensive surveillance of this species is needed to control the further dissemination.